Enhancing field education of social work in Mainland China: perspectives from students and faculty members. Issue 3 (2nd September 2021) - Liu, Meirong; Sun, Fei; Zhang, Zhaoyu; Jiang, Guohe; Marsiglia, Flavio F.; Pantovich, Tiahna
ABSTRACT: As part of the CSWE-China Collaborative, this article reports the outcomes of collaborative effort among two U.S. social work programmes and their partner schools in central China. It examines the challenges in social work field education through an indigenous perspective and offers suggestions through a cross-cultural lens. Using a mixed-method approach, we explored the perspectives of students and faculty members in central China. The survey included 200 students and 72 faculty members, and one focus group was conducted with eight faculty members. The identified challenges included low preparedness among students, lack of supportive resources from schools, unavailability of qualified supervisors and internship agencies and lack of environmental support. The solutions included providing students with orientations and ongoing support, enhancing faculty competencies, strengthen school-agency connections and implementing initiatives to increase the status of social work as a profession through evidence- and valued based social work practice.